Effects of microsatellite instability on recurrence patterns and outcomes in colorectal cancers - Kim, Chang Gon (Br J Cancer, 2016)
BACKGROUND: Among colorectal cancers (CRCs), high-frequency microsatellite instability (MSI-H) is associated with a better prognosis, compared with low-frequency MSI or microsatellite stability (MSI-L/MSS). However, it is unclear whether MSI affects the prognosis of recurrent CRCs. METHODS: This study included 2940 patients with stage I–III CRC who underwent complete resection. The associations of MSI status with recurrence patterns, disease-free survival (DFS), overall survival from diagnosis to death (OS1), and overall survival from recurrence to death (OS2) were analysed. RESULTS: A total of 261 patients (8.9%) had MSI-H CRC. Patients with MSI-H CRC had better DFS, compared to patients with MSI-L/MSS CRC (hazard ratio (HR): 0.619, P<0.001). High-frequency microsatellite instability CRC was associated with more frequent local recurrence (30.0% vs 12.0%, P=0.032) or peritoneal metastasis (40.0% vs 12.3%, P=0.003), and less frequent lung (10.0% vs 42.5%, P=0.004) or liver metastases (15.0% vs 44.7%, P=0.01). Recurrent MSI-H CRC was associated with worse OS1 (HR: 1.363, P=0.035) and OS2 (HR: 2.667, P<0.001). An analysis of patients with colon cancer yielded similar results. CONCLUSIONS: Recurrence patterns differed between MSI-H CRC and MSI-L/MSS CRC, and recurrent MSI-H CRCs had a worse prognosis.